2018
DOI: 10.1007/s11065-018-9388-2
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Deficits in Psychotic Disorders: A Lifespan Perspective

Abstract: Individuals with disorders that include psychotic symptoms (i.e. psychotic disorders) experience broad cognitive impairments in the chronic state, indicating a dimension of abnormality associated with the experience of psychosis. These impairments negatively impact functional outcome, contributing to the disabling nature of schizophrenia, bipolar disorder, and psychotic depression. The robust and reliable nature of cognitive deficits has led researchers to explore the timing and profile of impairments, as this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
239
3
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 347 publications
(267 citation statements)
references
References 268 publications
(467 reference statements)
17
239
3
8
Order By: Relevance
“…Previous studies have demonstrated that people with psychosis have deficits in a wide variety of cognitive domains, in particular intelligence (72). In addition, such deficits are present in the premorbid stage and in the prodromal or at-risk mental phase, and predict the emergence of full-blown psychosis (73,74). Therefore, to real understanding the psychosis liability it is relevant to gather information of IQ, because it is a multidimensional phenotype that requires cognitive, affective, psychophysiological, social, and behavioral variables.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that people with psychosis have deficits in a wide variety of cognitive domains, in particular intelligence (72). In addition, such deficits are present in the premorbid stage and in the prodromal or at-risk mental phase, and predict the emergence of full-blown psychosis (73,74). Therefore, to real understanding the psychosis liability it is relevant to gather information of IQ, because it is a multidimensional phenotype that requires cognitive, affective, psychophysiological, social, and behavioral variables.…”
Section: Discussionmentioning
confidence: 99%
“…In schizophrenia, schizoaffective disorder, bipolar I disorder, and schizotypal personality disorder, cognitive deficits were doc­u­mented in all domains: sensorimotor, attention, learning and memory, executive functions, language, and social cognition 180‐184 . These deficits were most pronounced in schizophrenia, but the other disorders showed a similar, although less extreme, profile of cognitive impairment 185‐188 . With regard to dimensions, negative and disorganized symptoms were linked to all aforementioned deficits, whereas reality distortion was essentially unrelated to cognitive impairment 189‐191 .…”
Section: Validity Evidencementioning
confidence: 99%
“…(21,22,23) Our testing for cognitive impairment associated with psychosis or aggressive behavior showed no statistical significance before and after the use of antipsychotics followed by the reduction of symptoms as seen in other psychotic disorders. (24) Even though cognition testing may be affected through agitation and deficiencies in communication, we found that the sole use of MMSE doesn't account for a full cognitive test battery in severe dementia.…”
Section: Discussionmentioning
confidence: 75%